Una mirada al neopolicial latinoamericano: Mempo Giardinelli, Leonardo Padura y Paco Ignacio Taibo II - Martín Escribá, Àlex; Sánchez Zapatero, Javier (Anales de Literatura Hispanoamericana, 2008)
Mempo Giardinelli, Leonardo Padura and Paco Ignacio Taibo II are three of the most outstanding representatives of Latin-American fiction called neopolical. In spite of belonging to different national traditions, their works belong to the big space of neopolicial. Social and realistic, the novels written by Giardinelli, Padura and Taibo II form a critical view of Latin-American present. So, these three writers are doing a contracultural speech capable to show the reality of Argentina, Cuba and Mexico.
Keywords: Mempo Giardinelli; Leonardo Padura; Paco Ignacio Taibo II; Crime story; Latin-American; Crime story (neopolicial); Realism; Critic; Social novel